The Novel Peptide AEDPPE Alleviates Trophoblast Cell Dysfunction Associated With Preeclampsia by Regulating the NF-κB Signaling Pathway - Wang, Yixiao; Cao, Yan; Ji, Xiaohong; Li, Ting; Xue, Lu; Li, Chanjuan; Jia, Ruizhe; Ding, Hongjuan (Frontiers in Cardiovascular Medicine, 2021)
ABSTRACT Background: Preeclampsia (PE) is a serious risk to the health of pregnant women and fetuses during pregnancy, and there is no effective treatment for this condition. Currently, many reports have confirmed the therapeutic effects of peptides in diseases, but the role of peptides in PE is still poorly understood. Methods: The peptide AEDPPE is derived from heat shock protein beta-1 (HSPB1), amino acids 100 to 109 (DVNHFAPDEL), which was identified in our previous study. We synthesized AEDPPE and investigated the effect of AEDPPE on HTR-8/SVneo cell function by Cell counting kit-8, flow cytometry assay, Transwell and wound healing assays. qRT-PCR and ELISA assays were used to determine cytokine expression. Pull down assay, mass spectrometry, Western blotting and immunofluorescence were used to explore the potential target and signaling pathway regulated by AEDPPE. Finally, the effect of AEDPPE on lipopolysaccharide (LPS)-induced PE-like rat model was assessed. Results: AEDPPE significantly promoted the migration and invasion of HTR-8/SVneo cells and decreased the expression of interleukin Iβ (IL-1β), interleukin 6 (IL-6), and interleukin 8 (IL-8). These functions performed by AEDPPE remained evident after damage to HTR-8/SVneo cells with tumor necrosis factor alpha (TNF-α) and AEDPPE reversed the elevated sFlt-1/PIGF ratio induced by TNF-α. AEDPPE may exert these biological effects by binding to heat shock protein 90β (HSP 90β) and thus affecting NF-κB signaling pathway. In LPS-induced PE-like rat model, AEDPPE significantly improves rat symptoms and fetal rat outcomes. Conclusion: Our study shows that AEDPPE enhances trophoblast migration and invasion and reduces inflammatory cytokine expression, which may involve the NF-κB signaling pathway. AEDPPE may become a new approach to PE treatment.